2014
DOI: 10.1002/chem.201402548
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐Selective Catalysis

Abstract: Substrate selectivity is an important output function for the validation of different enzyme models, catalytic cavity compounds, and reaction mechanisms as demonstrated in this review. In contrast to stereo-, regio-, and chemoselective catalysis, the field of substrate-selective catalysis is under-researched and has to date generated only a few, but important, industrial applications. This review points out the broad spectrum of different reaction types that have been investigated in substrate-selective cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 176 publications
(251 reference statements)
1
27
0
Order By: Relevance
“…We briefly demonstrated that the library screening can also produce substrate‐optimized catalysts that can be used to selectively convert one substrate in the presence of structurally similar compounds (Figure ) . For example, an equimolar mixture of glucose‐derived diol 6 and the analogous mannose derivative 10 yielded a hardly separable mixture of the benzoates 7 a , 7 b , 11 a and 11 b when treated with Bz 2 O and catalytic amounts of DMAP.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We briefly demonstrated that the library screening can also produce substrate‐optimized catalysts that can be used to selectively convert one substrate in the presence of structurally similar compounds (Figure ) . For example, an equimolar mixture of glucose‐derived diol 6 and the analogous mannose derivative 10 yielded a hardly separable mixture of the benzoates 7 a , 7 b , 11 a and 11 b when treated with Bz 2 O and catalytic amounts of DMAP.…”
Section: Figurementioning
confidence: 99%
“…[18] We briefly demonstrated that the library screening can also produce substrate-optimized catalysts that can be used to selectively convert one substrate in the presence of structurally similar compounds (Figure 4). [19] For example, an equimolar mixture of glucose-derived diol 6 and the analogous mannose derivative 10 yieldedahardly separable mixture of the benzoates 7a, 7b, 11 a and 11 b when treated with Bz 2 Oa nd catalytic amounts of DMAP.O nt he contrary,o ur best hit from the library was Ac-Lys-Leu-Leu-Gln-Ala-Pro-5-NH 2 ,w hich gave an excellents electivity for the formation of the benzoylated glucoside 7a while leaving mannoside 10 mostly untouched (Figure 4a). On ap reparative scale, we were able to isolate 7a in 91 %y ield, and 52 %o ft he starting compound 10 could be recovered under the reaction conditions: 6 (1 equiv), 10 (1 equiv), Ac-Lys-Leu-Leu-Gln-Ala-Pro-5-NH 2 (10 mol %), Bz 2 O (5 equiv), NEt 3 (15 equiv), À15 8C, 38 h, CHCl 3 .A lthough most of the substrates we tested so far were derived from carbohydrates, our concept is not restricted to this class of substrates.…”
mentioning
confidence: 99%
“…[10] Surprisingly, few catalytic systemsh ave proved successfuli n substrate-selective catalysis, in which the active catalysti sa ble to discriminate between similars ubstrates by modifying the substrate reactivity patterns. [11] Such ac oncept, which is reminiscento ft he highly substrate selective processes occurring in enzymes,i se xtremely difficult to mimic in non-natural transition metal catalysis [12] and it is mainlya ssociated with the high inner reactivity of transition metal complexes,w hich makesi t difficult to discriminate between chemically similars ubstrates. [13] Herein, we report as trategyt hat is based on as et of supramolecular palladium catalysts that are stereo-electronically identical with am inimal variation in the nature of ac ation located eight chemical bonds apart from the catalytically active sites.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we explored the catalytic effect of certain substrate‐specific4 ruthenium–porphyrin complexes, which display lactam‐based hydrogen‐bonding ligands 5. We have stressed the enzyme‐like character of their supramolecular arrangement,6 in which the lactam acts as a binding pocket and the transition metal as a prosthetic group.…”
Section: Influence Of the Ligand Configuration On The Enantioselectivmentioning
confidence: 99%